Performance of okra and soil using indigenous microorganisms inoculants - Rubini Devi Selvarajoo,; Nurul ‘Azyyati Sabri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Microbial inoculants are beneficial microorganisms applied to plants or the soil to promote plant growth and control pest disease and weeds. Microbial inoculants isolated from local surroundings are indigenous microorganisms (IMO) inoculants. The performance of the IMO inoculants is varied depending on the sources and the local environment. Therefore, it is important to identify the right sources to enhance the efficiency of the IMO inoculants. This research aims to study the performance of okra and soil by mixing potential yeast sources for indigenous microorganisms (IMO) inoculants. Longan and mango were chosen as the sources of yeasts. The IMO inoculants were fermented for a week, and the microorganisms group was identified. Then, the IMO inoculants were applied to the okra and tested for physical and mineral content analysis. IMO inoculants with mango and longan showed a higher yeast population than the control. However, IMO inoculants with mango showed the best plant growth and harvesting time performance. The soil treated with both IMO inoculants also showed higher potassium and calcium. To conclude, plants treated with both IMO inoculants performed better than the control. Thus, IMO inoculants with longan and mango may potentially enhance the yeast community in IMO inoculants, indirectly improving okra growth and benefiting the agriculture field in the future.